2017
DOI: 10.1016/j.celrep.2017.07.044
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Sp3 Cooperates with HDAC2 to Regulate Synaptic Function and Plasticity in Neurons

Abstract: The histone deacetylase HDAC2, which negatively regulates synaptic gene expression and neuronal plasticity, is upregulated in Alzheimer's disease (AD) patients and mouse models. Therapeutics targeting HDAC2 hold promise for ameliorating AD-related cognitive impairment; however, attempts to generate HDAC2-specific inhibitors have failed. Here, we take an integrative genomics approach to identify proteins that mediate HDAC2 recruitment to synaptic plasticity genes. Functional screening revealed that knockdown of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 55 publications
3
60
0
Order By: Relevance
“…Indeed, how multiple HDAC isoforms affect learning and memory has been elucidated. For example, HDAC2, negatively regulates hippocampal-dependent memory (Guan et al, 2009;Yamakawa et al, 2017). Recently, it was found that the enzyme acetyl-CoA synthetase 2 (ACSS2) binds to promoters of neuronal activity and memory-related genes where it locally catalyzes the production of acetyl coenzyme A (Acetyl CoA) from acetate, coenzyme A (CoA), and ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, how multiple HDAC isoforms affect learning and memory has been elucidated. For example, HDAC2, negatively regulates hippocampal-dependent memory (Guan et al, 2009;Yamakawa et al, 2017). Recently, it was found that the enzyme acetyl-CoA synthetase 2 (ACSS2) binds to promoters of neuronal activity and memory-related genes where it locally catalyzes the production of acetyl coenzyme A (Acetyl CoA) from acetate, coenzyme A (CoA), and ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work using a murine hippocampal model demonstrates a role for histone acetylation and subsequent expression of neuronal genes involved in memory formation (Mews et al 2017). In mammals, Sp3 has been shown to recruit HDAC2 to synaptic specific genes, without interfering in other HDAC2 gene targets (Yamakawa et al 2017(Yamakawa et al , 1319(Yamakawa et al -1334. Together, these findings suggest the presence of specific recruitment factors that dictate the acetylation state of cell-type specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…We identify one such gene, Endo-B1, for which the neuronspecific isoforms are selectively decreased in AD (37). It remains to be determined whether HDAC2 regulates Endo-B1b/c levels through transcriptional repression as demonstrated for the regulation of synaptic proteins by HDAC2 (15,40). Our preliminary experiments demonstrate that HDAC2 knockdown in cultured neurons increases levels of mRNA for both neuron-specific (Endo-B1b and Endo-B1c) and ubiquitously expressed (Endo-B1a) isoforms (unpublished observation).…”
Section: Hdac2 Regulates Endo-b1 Expression and Aβ Toxicitymentioning
confidence: 94%